AB0331 Analysis of the effectiveness of different doses of rituximab in a cohort of patients with rheumatoid arthritis. (23rd January 2014) - Manrique-Arija, S.; Fernandez-Nebro, A.; Coret, V.; Nieves, L.; Rodriguez-García, V.; Romero-Barco, C. M.; Ureña, I.; Jimenez-Nuñez, F.; Cano, L.; Belmonte, M. A.; Irigoyen, M. V.
Abstract : Objectives: To evaluate the effectiveness of Rituximab(RTX) in patients with rheumatoid arthritis(RA) depending on the dose of drug used. Methods: Design : Retrospective, observational study. Patients: RA(ACR/EULAR criteria) >18 yrs, treated with at least 1 dose of RTX, in follow-up on service of Rheumatology of the HRU Carlos Haya of Málaga(Spain). Those patients with less than 3 months of follow-up from the first dose of RTX were excluded. Groups of treatment according to the doses of RTX: Group 1: 2 infusions of 1 g separated by 15 days (2x 1g); Group 2: cycles of 2x1g followed by cycles of 0.5g, separated by 15 days (2x0.5 g);Group 3: 2x0, 5g cycles. The repetitions of cycles were on demand according to the clinical situation. Outcomes: Main Variable: Time in RTX treatment. Secondary Variable:No. of cycles adjusted by follow-up time. Definitions: time in RTX treatment was calculated as the number of the days between the date of the first infusion and the date on which RTX was definitively stopped or the date of last visit if the treatment still continues. Clinical follow-up: The data of variables related activity (DAS 28, HAQ), security (type and number of adverse events) and concomitant treatment were collected in each visit. Statistical analysis : A descriptive analysis and a comparison between groups of treatment using ANOVA/Kruskal wallis or Chi square/Fisher's exact test were conducted. The time in RTX treatment was analyzed by Kaplan Meyer curve and the comparison between groups, by log rank test. The numbers of cycles of RTX adjusted by follow-up time using incidence rates(IR) and compared by using incidence rate ratio(IRR) were evaluated. Multivariate analysis using Cox regression model was conducted. Results: 52 patients were included. There were no differences between the different treatment groups in the baseline characteristics of the patients(age, RF, Anti CCP, erosions, number of DMARDs or biologic therapy, orthopedic surgeries, DAS28 and HAQ) except in sex [group1: 10(71.4%), group 2: 26(100.0%) group 3: 11(91.7); p=0, 010] and in the order of the RTX between used biological therapies (It was used as a 2nd line of treatment or later in 9 patients (64.3%) of group 1, 25(96.2%) group 2 and 11(91.7%)group 3; p= 0, 014). Patients treated with RTX were followed during 135.3 patient-years with an average (SD) of 31.2(18) months, and a mean IR of 1.53 cycles/patient-years (CI 95% 1.32-1.73). Differences in the IRR between groups of treatment were found [Group 1 Vs group 2 : IRR(CI95%)= 0.61 (0.42 to 0, 87), P=0.0056; Group 2 Vs group 3: 0.77 (0.51 to 1, 17), p= 0.2283; and Group 1 Vs group 3: 0.47 (0.29 to 0, 77), p=0.0045). Group 2 presented better survival of RTX treatment [65.7 months (CI95%, 60.8-70.7)] that the Group 1 [33.5 (CI95%, 22.7-44.3)] and 3 [19.8 (CI95%, 14.1-25.4)], respectively (log rank test = 0.001). No basal variables that influenced the RTX follow-up time were identified in the multivariate analysis. Conclusions: The patients treated with cycles of 2x1g of RTX needed less cycles/patient-years in comparison with the other groups, but the effectiveness of RTX is higher in those who begin with 2x1g of RTX cycles followed by 2x0.5 g RTX cycles. Disclosure of Interest: S. Manrique-Arija Grant/research support from: Pfizer, A. Fernandez-Nebro: None Declared, V. Coret: None Declared, L. Nieves: None Declared, V. Rodriguez-García: None Declared, C. Romero-Barco: None Declared, I. Ureña: None Declared, F. Jimenez-Nuñez: None Declared, L. Cano: None Declared, M. Belmonte: None Declared, M. Irigoyen: None Declared